Characteristics and outcomes of peer consultations for assisted dying request assessments: Cross-sectional survey study among attending physicians - Stijn Vissers; Stijn Vissers; Sigrid Dierickx; Sigrid Dierickx; Luc Deliens; Luc Deliens; Freddy Mortier; Freddy Mortier; Joachim Cohen; Kenneth Chambaere; Kenneth Chambaere (Frontiers Media S.A., 2023)
BackgroundIn most jurisdictions where assisted dying practices are legal, attending physicians must consult another practitioner to assess the patient's eligibility. Consequently, in some jurisdictions, they can rely on the expertise of trained assisted dying consultants (trained consultants). However, these peer consultations remain under-researched. We examined the characteristics and outcomes of peer consultations to assess an assisted dying request with trained consultants, and explored how these characteristics influence the performance of assisted dying.MethodsWe conducted a cross-sectional survey in 2019-2020 in Belgium among attending physicians who had consulted a trained consultant for an assisted dying request assessment (N = 904).ResultsThe valid response rate was 56% (502/903). The vast majority of attending physicians (92%) who had consulted a trained consultant were general practitioners. In more than half of the consultations (57%), the patient was diagnosed with cancer. In 66%, the patient was aged 70 or older. Reported as the patients' most important reasons to request assisted dying: suffering without prospect of improving in 49% of the consultations, loss of dignity in 11%, pain in 9%, and tiredness of life in 9%. In the vast majority of consultations (85%), the attending physician consulted the trained consultant because of the expertise, and in nearly half of the consultations (46%) because of the independence. In more than nine out of ten consultations (91%), the consultant gave a positive advice: i.e., substantive requirements for assisted dying were met. Eight out of ten consultations were followed by assisted dying. The likelihood of assisted dying was higher in consultations in which loss of dignity, loss of independence in daily living, or general weakness or tiredness were reasons for the request.ConclusionOur findings indicate that the peer consultation practice with trained consultants is most often embedded in a primary care setting. Moreover, our study corroborates previous research in that assisted dying is performed relatively less frequently in patients with cancer and more often in patients with general deterioration. Our findings suggest that attending physicians hold peer consultations with trained consultants to endorse their own decision-making and to request additional support.